Identifying and Leveling the Factors Affecting the Maturity of the Organization's IT Using the Interpretive Structural Modeling and Fuzzy MICMAC Approach - Nazila Seddighi; Mohamad Reza Sanaei (مطالعات مدیریت کسب و کار هوشمند, 2020)
Considering the role of information technology maturity in increasing organizational competitiveness, this study aims to propose a model for identifying the factors affecting the IT organization processes based on the ITIL and COBIT frameworks, as well as determining the causal relationships and leveling these factors using a hybrid approach of ISM and Fuzzy MICMAC. This research is classified as a descriptive-survey, and applied research. researcher-made questionaries’ to collect data. The statistical population of this study consists of senior managers and senior experts of FANA Company. A limited number of experts can provide this study’s required information, the sample size was equal to the statistical population (consisting of 15 organizational experts). In order to demonstrate the capability of the proposed model, this model was implemented at Fantaff Company. The findings showed that, based on the factors mentioned in these frameworks and according to the organizational expert’s views, there are14 factors influencing the maturity of IT in this organization in the form of three areas of “strategy and planning of IT services”, “acquisition and implementation of IT services”, and “monitoring and supporting IT services”. In addition, after analyzing the causal relations among these factors, "applying standards in IT", "existence of organizational structure of IT", and "optimal network infrastructure and data center" were determined as the most effective, the most Affected, and the most independent factors in the IT maturity model of Iranian organizations, respectively, which played a significant role in determining the level of maturity of IT organizations.